PERSEPSI KONSUMEN TERHADAP WINE SALAK BALIWEIN - Putu Mira Astuti Pranadewi (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2020)
Salacca wine Baliwein is produced in a large quantity, but not many local people or foreign tourists know about this wine. Based on this condition, it is considered necessary to conduct a more in-depth study of the consumer perception of salacca wine so the result of this study can contribute to the development of this product. The objective of this research was to determine the perception of consumer toward Salacca Wine Baliwien. The research question to this study is how is the perception of the consumer toward Salacca Wine Baliwein. This Study uses 50 respondents from the customer who tasted the wine before. This Study Uses 6 indicators (sweetness, fruity flavor, acidity, tannin, alcohol, length or finish). The analysis used in this study is quantitative method. The analysis show that the consumer’s perception toward Salacca Wine Baliwein is 3,41 with good category. The highest index of perception is indicator acidity and length or finish (4,37 with good category) and the lowest index is indicator sweetness (1.04 with not very good category).